Revolutionizing Report and Complaint Services at South Sumatra Police Criminal Investigation Sub-Directorate III - Akil, Ibrahim; Sobri, KM; Sriati, Sriati; Putra, Raniasa (PERSPEKTIF, 2024)
Reporting and complaint services are important aspects of an effective and efficient law enforcement system. In this context, Sub-Directorate III of Criminal Investigation of the Regional Police of South Sumatra Province introduced innovative services to increase accessibility and responsiveness to the needs of the community in reporting crimes and submitting complaints. This research aims to examine the implementation and impact of this innovation. The research methods used include surveys, interviews, and document analysis to realize the success of innovation in improving service efficiency, speeding up case handling, and increasing public trust in the police. The findings show that innovation in reporting and complaint services has succeeded in reducing response times, increasing information transparency, and improving the image of law enforcement agencies. The results of this research provide a better understanding of the importance of innovation in public services in the law enforcement sector. It is hoped that the implications of these findings can become the basis for further development policies aimed at improving the effectiveness and efficiency of reporting and complaint services at the local, regional, and national levels.